Association between age at type 1 diabetes diagnosis and metabolic outcome at young adulthood: a real‐life observational study. Issue 1 (21st June 2020) - Goldberg, Tomer; Brener, Avivit; Levy, Sigal; Interator, Hagar; Laurian, Irina; Dorfman, Anna; Chorna, Efrat; Oren, Asaf; Eyal, Ori; Lebenthal, Yael
Abstract: Background: Younger age at diagnosis of type 1 diabetes (T1D) may affect the clinical course and outcome. We examined whether age at diagnosis was associated with glycemic control and metabolic outcome in young adulthood. Methods: This observational study included 105 young adults with T1D (current mean age: 21.2 ± 3.0 years, mean age at diagnosis 12.0 ± 4.0 years) followed during 2012 to 2019. Data on HbA1c, glucose variability, continuous glucose monitoring (CGM) metrics, body mass index (BMI), blood pressure (BP), and body composition were collected from medical records from age 18 years until last visit, and the association between age at diagnosis and outcomes was assessed. Results: Age at T1D diagnosis was negatively associated with HbA1c levels (r = −0.368, P = .001), BMI (r = −0.218, P = .026), and diastolic BP (r = −0.215, P = .028). Younger age at diagnosis predicted poorer glycemic control after controlling for T1D duration, sex, socioeconomic status, BMI, and CGM use (r 2 = 0.19, P = .002). There was a 0.1% greater HbA1c reduction for every yearly increase in age at diagnosis (β = −0.090, P = .042). The mean metabolic age of females diagnosed at <10 years of age was older than their chronological age ( P = .049). Conclusions: Younger age at T1D diagnosis predicts worse glycemic control at young adulthood, independent of recognized confounding risk factors (disease duration, sex, socioeconomic status, weight, and use of diabetes technology). Female patients diagnosed at a young age have an older metabolic age, indicating the need for lifestyle alteration to improve their basal metabolic rate.